Patient satisfaction analysis of BPJS at the balai makam community health center in bathin solapan subdistrict, bengkalis regency - Novi Nurmayanty; Elfindri Elfindri; Jasrida Yunita (Science Midwifery, 2023)
Patient satisfaction at the Balai Makam Public Health Center in Bathin Solapan Sub-district can be influenced by several issues experienced in healthcare services. To address these issues, this study was conducted with the aim of analyzing the level of patient satisfaction with BPJS (Social Health Insurance) at the Balai Makam Public Health Center. The research utilized a mixed-method approach, involving primary informants who were BPJS patients at the Balai Makam Public Health Center, supportive informants consisting of healthcare providers at the health center, and key informa nts who were responsible for the BPJS Pcare program at the Balai Makam Public Health Center. Primary data were obtained through questionnaires, in-depth interviews, and observations, while secondary data were obtained from profiles, programs, and patient visit reports. Data analysis was conducted using both quantitative and qualitative methods, employing univariate, bivariate, and multivariate analysis techniques. The research findings indicate that the majority of patients (52.1%) were dissatisfied with the provided services. Several factors influenced patient satisfaction at the Balai Makam Public Health Center. Variables significantly associated with patient satisfaction with BPJS at the Balai Makam Public Health Center in Bathin Solapan Sub-district included reliability (p-value 0.002; OR= 7.581), responsiveness (p-value 0.000; OR= 14.069), assurance (p-value 0.000; OR= 20.160), tangibles (p-value 0.001; OR= 4.885), and empathy (p-value 0.000; OR= 18.462). The variable that had the most significant impact on patient satisfaction was responsiveness to services after controlling for the empathy variable. Insufficient responsiveness to service had a risk up to 21 times higher in causing dissatisfaction among BPJS patients at the Balai Makam Public Health Center in Bathin Solapan Sub-district. Interview results indicated that the main factor influencing BPJS patient satisfaction was tangible evidence.